Underglobalization : Beijing's Media Urbanism and the Chimera of Legitimacy - Neves, Joshua, 1977- (Book collections on Project MUSE., 2020)
"UNDERGLOBALIZATION examines the cultural logic of the fake that has shaped globalized politics and culture in China. Joshua Neves shows how this interest in faking encompasses more than just China's infamous counterfeit luxury goods and pirated films, extending into questions about political legitimacy and Chinese ambivalence about being assimilated into hegemonic global modernity. Neves looks at various cultural practices in post-socialist Beijing-ranging from the consumption and circulation of cinema and film, to the proliferation of televisions and screens in private and public spaces, to the design of urban spaces and architectural landmarks-to understand how notions of legitimacy and faking operate as forms of neoliberal and neocolonial control. Pushing back against claims that Chinese modernity is incomplete, unrealized, or "counterfeit," Neves argues that the strategy of "faking globalization" deploys illegality and illegitimacy as cultural and political techniques of being global. Neves begins by outlining the history of Beijing's post-socialist transformation, showing how this transformation is structured temporally--as the ruins of the past have been cleared away--to make space for modern architectural projects and redesigned city spaces. He also explores how media culture influences and interacts with official designs and blueprints for these urban projects, a kind of fake or piratical citizenship that penetrates and transforms official structures. Next, turning to cinema and television, Neves looks at movie theaters in Beijing and the distribution and regulation of film in China, as well as at the proliferation of TV culture and screens throughout Beijing, showing how television becomes a form for public communication. Lastly, he considers how everyday people interact with media and technology in China, focusing on the role of laborers and how they engage creatively with the media technologies they help produce, and finally returning to the question of media piracy to explore the social life of informal media as it circulates through Beijing. UNDERGLOBALIZATION will be of interest to scholars and students in Asian studies, media studies, and cultural studies"--